2008
DOI: 10.3398/1527-0904(2008)68[374:iopgmo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pocket gopher mounds on nonnative plant establishment in a shrubsteppe ecosystem

Abstract: ABSTRACT.-Soil disturbances across a wide range of spatial scales have been found to promote the establishment of invasive plant species. This study addresses whether mounds built by northern pocket gophers (Thomomys talpoides) in the shrubsteppe environment of north central Washington are facilitating plant invasions into native-dominated fields. Research was conducted in native-dominated plant communities adjacent to ex-arable, nonnative-dominated fields. To determine the effect of mounds on plant growth, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Beneath shrub canopies, mounds may have decreased soil moisture due to the significant reduction in organic matter content, which is positively associated with the water-holding capacity of the soil (Hudson, 1994). Kyle et al (2008) reported a similar pattern in a shrub-steppe ecosystem, where pocket gopher mounds favoured plant invasion while reducing soil moisture and N mineralization rates. Low soil moisture limits mineralization of organic nutrients on mounds (Sherrod & Seastedt, 2001); this may represent somewhat stressful, yet transient, conditions for plant growth, particularly for native species (Figure 6b).…”
Section: Exotic Species Patternsmentioning
confidence: 59%
“…Beneath shrub canopies, mounds may have decreased soil moisture due to the significant reduction in organic matter content, which is positively associated with the water-holding capacity of the soil (Hudson, 1994). Kyle et al (2008) reported a similar pattern in a shrub-steppe ecosystem, where pocket gopher mounds favoured plant invasion while reducing soil moisture and N mineralization rates. Low soil moisture limits mineralization of organic nutrients on mounds (Sherrod & Seastedt, 2001); this may represent somewhat stressful, yet transient, conditions for plant growth, particularly for native species (Figure 6b).…”
Section: Exotic Species Patternsmentioning
confidence: 59%
“…Shifts may occur stochastically or because disturbances favour organisms with particular resource requirements or traits relating to colonization and disturbance tolerance (Eldridge & James, ). Past studies have generally observed a shift towards more annual plant dominated communities (Eldridge & Simpson, ; Kyle, Kulmatiski, & Beard, ; Moroka, Beck, & Pieper, ). While disturbances often support distinct species assemblages, overall richness may not change.…”
Section: Discussionmentioning
confidence: 99%
“…This not only includes herbivory by arthropods and nematodes (Seastedt et al 1988), but also by mammals (e.g., the pocket gopher Geomys bursarius, the 13-lined ground squirrel Spermophilus tridecemlineatus (Thorne and Andersen 1990;McMillian et al 1997)) who live in the soil-eating plants, turn the soil over (up to 30% of a prairie ground surface can be turned over every year: Kyle et al 2008), and, consequently, change prairie plant recruitment, composition (Forbis et al 2004), biomass, and species richness (Rogers et al 2001). Soil turnover by itself has been demonstrated to enhance invasive plant establishment (D'Antonio et al 1999) and productivity (Collins & Steinauer 1998).…”
Section: Introductionmentioning
confidence: 99%